Effects of reproductive and sociodemographic factors on obesity in Turkish women: a pilot study - Bayram, Sinem; Köseler, Esra; Kızıltan, Gül; Akçil Ok, Mehtap; Yeşil, Esen; Köse, Beril; Özdemir, Merve; Müftüoğlu, Selen; Saka, Mendane; Aksoydan, Emine; Tayfur, Muhittin; Türker, Perim Fatma; et al. (Progress in Nutrition, 2019)
Background and aim: Obesity has become a global epidemic. The current research aimed to determine sociodemographic and reproductive predictors of obesity among Turkish women. Materials and methods: Eligible subjects (n:833) were 40-64 years-old women living in Turkey. A questionnaire consisted of questions about sociodemographic and reproductive factors and the International Physical Activity Questionnaire were applied to participants by face to face interviews. Multivariate logistic regression examined the risk of being obese with a range of sociodemographic and reproductive factors. All analyses were performed with SPSS software (version 17.0; SPSS, Chicago, Ill., USA). Results: The mean BMI of women aged 51-64 years was 30.59±6.35 kg/m2. After adjustments for all other variables, increased obesity risk remained significant in women who had two children, housewifes, minimum active ones, ex smokers and had less than high school education. For multiple regression analysis sociodemographic factors from the bivariate analyses were entered, controlling for menarch age, menopausal age, hormone RT, parity, number of stillbirth, abortion. There was significant association between family income, occupation, education and BMI. Conclusion: In summary these findings showed comparable patterns of association of sociodemographic and reproductive factors with obesity in Turkey. Specific healthy lifestyle counseling is important for decreasing obesity in childbearing age women.